Transition in the complex and chaotic international systems: Iran - فرهاد قاسمی (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2018)
Transition in the international system is a prevalent and inevitable process and theories of international relations really pay attention to this. But development of international system and emergence of complex and chaotic system make a change in power transition model and this change requires a new explanation. On the other way Iran is among the countries that because of centrality in some regional orders and its internal dynamics is directly affected to these transition models. Therefore this article focuses on these questions that how transition in the complex and chaotic international system is explained and what are threats of Iran in new power transition model and how transition control model is applied by it? In respond to these questions the author believes that transition is directly linked to features of complexity as include bifurcation of order.in this respect author recognizes bifurcated transition as main feature of transition in these systems and suggests bifurcated transition model as new concept to international relations literature. Research method in this article is focused on critical realism and deduction and abduction and based on this, firstly the rules and algorithms of complex and chaotic systems will be characterized and then these rules are combined in new model as bifurcated transition model.